Methods of organizing society for people with disabilities: models of disability - Antonina Liovochkina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2016)
The article has realized the theoretical analysis of the problem of social organization for people with disabilities. The article defines the effective model of disability. We have also considered inefficient model that can bring harm to the person with disabilities. Among the effective and fruitful disability models identified the following: the social model, the capacity strengthening, socio-legal (political and legal) model of disability, as well as the model of disability from the standpoint of cultural pluralism.
Keywords: people with disabilities; the medical model of disability; the social model of disability; social support of people with disabilities